Synthesis of 3H-Pyrrolo[2,3-c]quinoline by Sequential I2-Promoted Cyclization/Staudinger/Aza-Wittig/Dehydroaromatization Reaction - Zou, Fakai; Pei, Fei; Wang, Liping; Ren, Zhilin; Cheng, Xiaohong; Sun, Yang; Wu, Jing; He, Ping (Synlett, 2019)
A facile synthetic approach to access of 3H-pyrrolo[2,3-c]quinoline derivatives has been achieved by a sequential I2-promoted cyclization/Staudinger/aza-Wittig/dehydroaromatization reaction. The targeted products were received in moderate to good yields (62–81%). The broad substrate scope and easy availability of the starting materials make this method a valuable tool for generating 3H-pyrrolo[2,3-c]quinoline products.
Keywords: 3H-pyrrolo[2,3-c]quinolines; I2-promoted cyclization; aza-Wittig reaction; azides; dehydroaromatization